Peran “Istri Yang Cakap” dalam Meningkatkan Perekonomian Keluarga pada Masa Pandemi Covid-19 - Vera Herawati Siahaan; Mariati Br. Barus (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2021)
A capable wife in Proverbs 31: 10-31 and 1 Peter 3: 1 is a wife that wives today can emulate. Her godly life, how she arranges her family's economy, how she plans to prepare for the future of her family members, how she is obedient and submissive to her husband, and how she can please her husband really shows that she is a special woman, who is expensive as in verse 10 said to be a pearl that is difficult to find. This journal describes the analytical writing method with a qualitative approach. The analysis carried out is in the form of an analysis of the study of the Old Testament Fiman in Proverbs 31: 10-31 and the New Testament 1 Peter 3: 1 concerning the idea of a wise woman and obedient and submissive women. This related competent text is very helpful in improving the family economy, especially in this pandemic. So this journal describes how a capable wife is, how she allows her husband's heart, how she can become a good planner who is very helpful in meeting the needs of her household. And what he did all because of his marriage commitment. AbstrakIstri yang cakap dalam Amsal 31:10-31 dan 1 Petrus 3 : 1 merupakan istri yang boleh diteladani oleh para istri zaman sekarang. Hidupnya yang saleh, bagaimana dia menata perekonomian keluarganya, bagaimana dia merencanakan untuk persiapan masa depan anggota keluarganya, bagaimana ia taat dan tunduk pada suami serta bagaimana dia boleh berkenan kepada suaminya sangat menunjukkan kalau dia adalah seorang wanita yang istimewa, yang mahal sebagai mana dalam ayat 10 dikatakan sebagai mutiara yang sulit untuk ditemukan. Jurnal ini menjelaskan metode penulisanan alisis dengan pendekatan kualitatif. Analisis yang dilakukan berupa analisis studi Fiman Perjanjian Lama dalam Amsal 31:10-31 dan perjanjian Baru 1 Petrus 3:1 tentang ide wanita bijak dan wanita taat dan tunduk. Teks terkait yang cakap ini sangat menolong dalam peningkatan perekonomian keluarga khususnya dalam masa pandemiini. Maka itu dalam jurnal ini di paparkan bagaimanakah istri yang cakap itu, bagaimanadia memperkenankan hati suaminya, bagaimana dia boleh menjadi seorang perencana yang baik yang sangat menolong dalam memenuhi kebutuhan rumah tangganya. Dan apa yang dilakukannya semua karena komitment pernikahan.